Impact of financial leverage on the firm performance in Malaysia company - Lee, Jing Ni (Universiti Malaysia Sarawak (UNIMAS), 2015)
Financial leverage can be defined where the company apply fixed income securities such as preferred equity and debt. It involves the raising of funds through financial activities. The use of financial leverage will help to boost and enhance the financial performance of the firm. This study aims to study the impact of financial leverage towards the firm performance in Malaysia Company. In addition this study also meant to investigate the relationship between debt ratio, debt-equity ratio and net working capital on return on asset. A sample of time series data on one firm for the period of 2006 first quarter until 2014 second quarter is conducted for this study. It is about 34 observations. For the purpose of this study, ARCH Heteroskedasticity Test, CUSUMof- Squares test, Jarque-Bera Normality test (JB), Breusch-Godfrey Serial Correlation LM Test, Ramsey RESET test, and Granger Causality Test is applied for further analysis. The results claim that there is a significant negative relationship found between debt ratio (DR) and return on asset (ROA). The results also indicate that there is a significant negative impact on debt-equity ratio (DER) on return on asset (ROA). In contrast, a significant positive relationship is found between net working capital (NWC) and return on asset (ROA).